2007
DOI: 10.1016/j.devcel.2007.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian SEPT2 Is Required for Scaffolding Nonmuscle Myosin II and Its Kinases

Abstract: Mammalian septin SEPT2 belongs to a conserved family of filamentous GTPases that are associated with actin stress fibers in interphase cells and the contractile ring in dividing cells. Although SEPT2 is essential for cytokinesis, its role in this process remains undefined. Here, we report that SEPT2 directly binds nonmuscle myosin II (myosin II), and this association is important for fully activating myosin II in interphase and dividing cells. Inhibition of the SEPT2-myosin II interaction in interphase cells r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
257
3
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(269 citation statements)
references
References 45 publications
7
257
3
2
Order By: Relevance
“…The herein proposed targeting pathway differs from those found in other eukaryotic cells by directing myosin assembly very early to the predetermined site of the future cell separation. However, the movement of myosin to the assembly site, the role of the septins in targeting and anchorage as well as the existence of higherorder structures of myosin are conserved features among yeast and other eukaryotic cells (Goldbach et al, 2010;Joo et al, 2007;Kosako et al, 2000;Matsumura, 2005;Vale et al, 2009;Yumura, 2001;Yumura et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The herein proposed targeting pathway differs from those found in other eukaryotic cells by directing myosin assembly very early to the predetermined site of the future cell separation. However, the movement of myosin to the assembly site, the role of the septins in targeting and anchorage as well as the existence of higherorder structures of myosin are conserved features among yeast and other eukaryotic cells (Goldbach et al, 2010;Joo et al, 2007;Kosako et al, 2000;Matsumura, 2005;Vale et al, 2009;Yumura, 2001;Yumura et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…We next examined the subcellular localization of septin2 during meiotic maturation by immunofluorescent staining using septin2 antibody (a gift from William S. Trimble) that has been described in a previous publication. 33 We did not observe any specific staining of septin2 in GV oocytes (data not shown). At Pro-M I and M I, septin2 decorated the entire length of the meiotic spindle.…”
Section: Resultsmentioning
confidence: 70%
“…32 It has been proposed that septin2-containing filaments serve as scaffold for myosin II and its kinase to ensure the full activation of myosin II that is necessary for the final stages of cytokinesis. 33 In addition, septin2-containing filaments were also colocalized with microtubules in the midbody, the central spindle, and the entire length of the spindle. [34][35][36] RNAi for septin2 or overexpression of truncated fragments of septin2 does not affect microtubule organization.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The decrease in the adiabatic bulk modulus for cells within metaphase may be due to the known change of actins, septins, and lamins from mechanical stress-bearing roles to alternate functions during mitosis, including cleavage furrow formation, extension of spindle fibers, and priming the nuclear envelope to reassemble postmitosis. [41][42][43] Additionally, a study found that the microtubule network is rearranged in metaphase such that the loadbearing axis of microtubules is arranged parallel to the substratum 44 and therefore perpendicular to the axis of the cell for which the adiabatic bulk modulus measurement is taken. These factors, coupled with the absense of an intact nucleus 10 serving as a scaffold for the cytoskeleton via linkage proteins such as plectin and nesprin-3, 45 likely account for the lowered adiabatic bulk modulus for cells within metaphase.…”
Section: Discussionmentioning
confidence: 99%